Outrage The Rise of Religious Offence in Contemporary South Asia - Rollier, Paul; Frøystad, Kathinka; Engelsen Ruud, Arild (UCL Press, 2019)
Whether spurred by religious images or academic history books, hardly a day goes by in South Asia without an incident or court case occurring as a result of hurt religious feelings. The sharp rise in blasphemy accusations over the past few decades calls for an investigation into why offence politics has become so pronounced, and why it is observable across religious and political differences. Outrage offers an interdisciplinary study of this growing trend. Bringing together researchers in Anthropology, Religious Studies, Languages, South Asia Studies and History, all with rich experience in the variegated ways in which religion and politics intersect in this region, the volume presents a fine-grained analysis that navigates and unpacks the religious sensitivities and political concerns under discussion.